2013
DOI: 10.1073/pnas.1317105110
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a simple theoretical model for protein folding with all-atom molecular dynamics simulations

Abstract: Advances in computing have enabled microsecond all-atom molecular dynamics trajectories of protein folding that can be used to compare with and test critical assumptions of theoretical models. We show that recent simulations by the Shaw group (10,11,14,15) are consistent with a key assumption of an Ising-like theoretical model that native structure grows in only a few regions of the amino acid sequence as folding progresses. The distribution of mechanisms predicted by simulating the master equation of this nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
112
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 65 publications
5
112
0
Order By: Relevance
“…2. This many-body feature allows this simple model to adequately describe the free-energy surfaces (3,6,18,38,39) and kinetics (17,39,40) of many proteins. An additional advantage of using this model is that the analytical forms of partition functions, Z WSME ðMÞ and Z WSME ðM DLD ; M ABD Þ, can be exactly derived (41,42); thus, free-energy surfaces and other quantities are readily calculated from Z WSME to obtain a clear view of the folding process.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…2. This many-body feature allows this simple model to adequately describe the free-energy surfaces (3,6,18,38,39) and kinetics (17,39,40) of many proteins. An additional advantage of using this model is that the analytical forms of partition functions, Z WSME ðMÞ and Z WSME ðM DLD ; M ABD Þ, can be exactly derived (41,42); thus, free-energy surfaces and other quantities are readily calculated from Z WSME to obtain a clear view of the folding process.…”
Section: Significancementioning
confidence: 99%
“…Therefore, emphasis on continuous regions that have the native-like configuration is an important feature of the WSME model and is also the reason why the model can describe the cooperativity among multiple residues in a suitable manner in single-domain proteins (17). However, with this emphasis on the many-residue effects, the WSME model may overestimate the cooperativity among residues in larger proteins.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…All-atom, explicit solvent micro to millisecond MD simulations [29][30][31] have in recent years significantly contributed to our understanding of disordered states of proteins 29,30,32,33 . Computational studies on KID protein using replica exchanged implicit solvent MD simulations 34 , and short all-atom MD simulations 35 showed that KID is largely unstructured and phosphorylation barely affects its helical propensity.…”
mentioning
confidence: 99%
“…Eaton and coworkers used this expanded version of the model to analyze in great depth the equilibrium and folding kinetics of the ultrafast folding villin headpiece subdomain (16). They then compared the folding pathways predicted by the fitted model with the results from long-timescale, all-atom simulations performed by the Shaw group (17). The comparison showed that the folding pathways observed in atomistic simulations involved local nucleation of native structure on no more than two regions, followed by the growth or closure of a single loop.…”
mentioning
confidence: 99%